STRATEGI PEMASARAN PANDAI BESI DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA MANDI ANGIN - Pusnita, Indah; Lubis, Bangun Paruhuman; Rengki, Rengki; Ningrum, Retno Dwi; Ninda, Nadia Ayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
Community service activities in the form of blacksmith marketing strategy training aim to increase production and marketing so as to encourage increased welfare of the people of Mandi Angin Village. The strategy used is to utilize digital platforms such as social media Instagram, Facebook and Shopee to market the product. Of course, it is supported by a unique design to attract customers to get to know and buy blacksmith products. Furthermore, the results of the training that has been carried out have had a positive impact on craftsmen, namely increasing their knowledge and skills, thereby encouraging them to be able to innovate and introduce their products to the wider community through social media and the marketplace.